Emotional detachment. Hegemony, causes, and aftermath - Hessen, Hemn Sharif Hessen (Sulaimani Journal for Humanities, 2025)
One of the types of divorce is emotional separation. Emotional separation as known as silent separation، an unannounced separation between husband and wife. This type of separation cannot be verified because there are no available statistics in the families. Therefore، statistical knowledge and research is necessary for this study. To this end، research is looking for reasons that lead to emotional separation. To get the statistic 100 married men and women in Sulaymaniyah who have been married for five years and are currently living with their spouses have been selected purposefully and answered the questionnaire، which consists of 24 questions. The results of the analysis showed that there were 41.6 emotional separations within families within the study boundaries.